2017
DOI: 10.1002/oby.21826
|View full text |Cite
|
Sign up to set email alerts
|

The TCN2 variant of rs9606756 [Ile23Val] acts as risk loci for obesity‐related traits and mediates by interacting with Apo‐A1

Abstract: The TCN2 variant acts as a risk factor for WC in the Arab population. The variant mediates obesity-related anthropometric traits via interactions with Apo-A1/high-density lipoprotein or TP53.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Therefore, our findings were not surprising as FTO may interact with ApoA1 in regulating weight, TBW, and SLM and thus affects obesity and also corroborate studies showing SNPs from ApoA1 associated with lower levels of HDL as obesity risk factors (Rashid and Genest, 2007;Chen et al, 2009). In addition, this is also supported by our previous observations showing interactions between Apo-A1/ HDL and a genetic variant in TCN2 regulate WC (Hebbar et al, 2017). Others have demonstrated a positive correlation between ApoB48 and abdominal circumference (Kuo et al, 2019), with obese and hyperlipidemic subjects showing higher levels of ApoB48 (Otokozawa et al, 2009).…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, our findings were not surprising as FTO may interact with ApoA1 in regulating weight, TBW, and SLM and thus affects obesity and also corroborate studies showing SNPs from ApoA1 associated with lower levels of HDL as obesity risk factors (Rashid and Genest, 2007;Chen et al, 2009). In addition, this is also supported by our previous observations showing interactions between Apo-A1/ HDL and a genetic variant in TCN2 regulate WC (Hebbar et al, 2017). Others have demonstrated a positive correlation between ApoB48 and abdominal circumference (Kuo et al, 2019), with obese and hyperlipidemic subjects showing higher levels of ApoB48 (Otokozawa et al, 2009).…”
Section: Discussionsupporting
confidence: 90%
“…To the best of our knowledge, the most commonly used Illumina Human OmniExpress Bead Chip genome wide array does not include the tested rs1997623 variant. Apparently, a vast majority of GWA studies were also performed in European, African-American and Asian population and relatively little information is available from the State of Kuwait (Hebbar et al, 2017, 2018). The genetic divergence of Kuwaiti population has largely been evidenced by the differences in disease prevalence and risk allele frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, in genome-wide disease association studies (GWAS), significance is confirmed after adjusting for confounding factors including age, gender, population stratification, and genetic ancestry. In our association analysis, age and gender were only adjusted as all study individuals belong to Arab ethnicity and their population structure has been well-defined in our previous genome-wide association studies 24,31,32. Since all three groups (lean, overweight, and obese) are only of Arabian descent, their haplogroup distribution should be similar to that of the Middle Eastern region.…”
Section: Discussionmentioning
confidence: 99%
“…All participants were recruited after obtaining written informed consent under protocols approved by the Scientific and Ethics Advisory Boards at the Dasman Diabetes Institute, Kuwait. The participant recruitment, sample collection, and related procedures were conducted in accordance with the Declaration of Helsinki and detailed elsewhere 23,24. On categorizing the study subjects based on BMI scores, we ended up with 232 obese (BMI≥30 kg/m 2 ), 110 overweight (BMI≥25 kg/m 2 and <30 kg/m 2 ), and 53 lean (BMI<25 kg/m 2 ) individuals.…”
Section: Methodsmentioning
confidence: 99%